TL 18166 - Evaluation of quality of life and radiological parameters after hallux valgus correction - Mansur, Henrique; Trindade Cardoso, Vinicius; Moreira de Castro Júnior, Isnar (Scientific Journal of the Foot & Ankle, 2019)
Introduction: The outcome of hallux valgus correction surgery is usually evaluated based on parameters of interest to the surgeon; however, the outcomes considered important by patients differ from those analyzed by physicians. Our objective is to evaluate the quality of life of patients undergoing hallux valgus correction and to assess the maintenance of radiographic parameters over time. Methods: The study included 38 patients who underwent hallux valgus correction surgery using different osteotomy techniques (scarf, chevron, arciform, proximal chevron and chevron-Akin) from January 2010 to December 2012. The patients were evaluated radiographically at 3 different times (preoperatively and 1 and 5 years postoperatively) and filled out the 36-Item Short Form Survey (SF-36) for the assessment of quality of life. Statistical analysis was performed using the paired Student’s t-test and the nonparametric Wilcoxon signed-rank and Friedman tests, with a maximum significance level of 5%. Results: Among the main findings of the SF-36 questionnaire, the sections on which the patients reported the best results were emotional role functioning, physical functioning and social role functioning, and the final mean score was 74.9. The metatarsophalangeal and intermetatarsal angles and medial eminence showed significant decreases during the postoperative period (p<0.05), and only 1 patient presented loss of joint congruence. Conclusion: Different surgical osteotomy techniques used to correct moderate and severe hallux valgus improved the patients’ radiological parameters and quality of life.